Evaluating the Efficacy of Sudarshan Kriya Yoga in Health Care: A Systematic Review of Randomized Controlled Trials - Giridharan, S; Soumian, Soni; Sudharsan, Srinivasan (International Research Journal of Ayurveda & Yoga, 2024)
Background: Sudarshan Kriya Yoga (SKY) is an advanced yogic breathing technique developed by the Art of Living Foundation. Given its widespread use in diverse therapeutic settings, a systematic review of randomized controlled trials (RCTs) was conducted to assess its efficacy in health care. Methods: This review followed the PRISMA guidelines and used the PECO framework. We searched databases such as the Web of Science, Cochrane Library, PubMed, and Scopus from the year 2000 to 2023 using a combination of MeSH phrases and free-text keywords. The inclusion criteria were restricted to RCTs involving any demographic, with SKY as the primary intervention. The risk of bias was assessed using the Cochrane Collaboration’s Risk of Bias 2.0 tool. Results: We included 15 RCTs and synthesized the results using quantitative analysis and qualitative narrative synthesis. The findings demonstrate significant improvements in psychological well-being, especially in stress reduction and emotional regulation across different populations. In addition, SKY also showed potential in managing symptoms of post-traumatic stress disorder and physiological markers such as blood pressure and heart rate variability. Conclusion: SKY effectively improves mental health and physiological parameters, highlighting its potential utility as a non-invasive therapeutic option. Despite its benefits, the studies varied in methodological rigor, indicating the need for further high-quality research to solidify these findings. Yoga, an ancient practice originating from India, has evolved over thousands of years into a popular holistic discipline that unifies body, mind, and spirit.[1] Initially focused on spiritual development and tranquillity, yoga is now globally recognized for enhancing physical flexibility, mental clarity, stress reduction, and overall well-being. As yoga has integrated into Western culture, a variety of styles have emerged, each emphasizing different elements such as physical postures (asanas), meditation (dhyana), and breath control (pranayama). Among these, Sudarshan Kriya Yoga (SKY), developed by the Art of Living Foundation, stands out for its unique use of rhythmic breathing